VISUAL OUTCOME IN EARLY VITRECTOMY FOR POSTERIOR PERSISTENT FETAL VASCULATURE ASSOCIATED WITH TRACTION RETINAL DETACHMENT. Issue 3 (March 2015) - Bosjolie, Angela; Ferrone, Philip
Abstract : Purpose: This study investigates the anatomical and visual outcome of vitrectomy for the treatment of unilateral posterior persistent fetal vasculature with associated traction retinal detachment in very young patients. Methods: A retrospective case series study from 1998 through 2010 of 11 eyes in 11 patients who underwent pars plana vitrectomy with or without lensectomy for unilateral posterior persistent fetal vasculature with traction retinal detachment affecting the macula. Results: Ten of the 11 patients (91%) received surgical intervention when 13 months old or younger (average age, 4 months). Postoperatively, 6 of 10 eyes (60%) had 20/800 or better vision, 2 of which had 20/60 vision. All 10 patients in this group had their retinas reattached postoperatively with significant reversal of retinal dragging. One of the 11 patients (9%) received surgical intervention for posterior persistent fetal vasculature at 33 months of age. This patient had persistent traction retinal detachment and a postoperative visual acuity of hand motion. Postoperative glaucoma was detected in 4 patients (36%). Conclusion: This study suggests that early intervention in patients with unilateral posterior persistent fetal vasculature with associated macula affecting traction retinal detachment may provide a better visual and anatomical outcome when vitrectomy and retinal reattachment are performed at a very early age. Abstract : This is a retrospective study of 11 patients with posterior persistent fetal vasculature and traction retinal detachment. Results suggest that pars plana vitrectomy when performed earlier than 13 months of age gives increased potential for retinal reattachment and functional visual acuity.